2014
DOI: 10.1152/ajpgi.00112.2014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of HIF-1α does not increase intestinal tumorigenesis

Abstract: The hypoxic response is mediated by two transcription factors, hypoxia-inducible factor (HIF)-1α and HIF-2α. These highly homologous transcription factors are induced in hypoxic foci and regulate cell metabolism, angiogenesis, cell proliferation, and cell survival. HIF-1α and HIF-2α are activated early in cancer progression and are important in several aspects of tumor biology. HIF-1α and HIF-2α have overlapping and distinct functions. In the intestine, activation of HIF-2α increases inflammation and colon car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…Microarray analysis was done as previously described (Xue et al, 2014). The full data set is available on the Gene Expression Omnibus database accession number GSE65104.…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analysis was done as previously described (Xue et al, 2014). The full data set is available on the Gene Expression Omnibus database accession number GSE65104.…”
Section: Methodsmentioning
confidence: 99%
“…Karhausen et al 8 showed that loss of epithelial HIF-1a led to severe intestinal inflammation, whereas an increase in epithelial HIF protein was protective. Xue et al 9 recently reported that activation of HIF-1a in intestinal epithelial cells did not increase intestinal tumorigenesis. Reduction of epithelial cell apoptosis in murine colitis by 1 inhibition of HIF-1 degradation by the hydroxylase inhibitor dimethyloxalylglycine underscores the importance of HIF-1 in the intestinal epithelium.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, HIF-2␣ is a transcriptional regulator of proinflammatory cyclooxygenase 2 (COX2) and microsomal prostaglandin E synthase (mPGES) to in-crease tumor inflammation, and treatment of HIF-2␣-overexpressing mice with the anti-inflammatory nimesulide can reduce colon tumorigenesis (47). Interestingly, HIF-1␣ activation has no effect on colon tumorigenesis (48). Similarly, we found that HIF-1␣ has no effect on the expression of Cxcl1.…”
Section: Discussionmentioning
confidence: 67%